2016
DOI: 10.1089/lgbt.2015.0031
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Antihomosexual Attitudes and Young Black Men Who Have Sex with Men in the South: A Need for Community-Based Interventions

Abstract: The findings suggest that cultural and community norms regarding antihomosexual attitudes may be a barrier to the practices of safe sex and a contributing factor to IPV among young Black MSM. There is a need for tailored interventions that address these cultural norms and establish social and community support for young Black MSM in Mississippi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…The associations between homonegative environments during adolescence and HIV risk demonstrated in the data adds to the existing body of knowledge on the relationships between homonegativity, environment, and health outcomes among Black GBMSM [19,[34][35][36][37]. Internalized homonegativity is mainly thought to negatively impact the physical and mental health of this population through pathways in which psychological distress leads to individual-level risk.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The associations between homonegative environments during adolescence and HIV risk demonstrated in the data adds to the existing body of knowledge on the relationships between homonegativity, environment, and health outcomes among Black GBMSM [19,[34][35][36][37]. Internalized homonegativity is mainly thought to negatively impact the physical and mental health of this population through pathways in which psychological distress leads to individual-level risk.…”
Section: Discussionmentioning
confidence: 75%
“…Prior research also points to experienced and internalized homonegativity as possible predictors of elevated HIV risk among Black GBMSM [11,13,[16][17][18]. A study of YB-GBMSM in Mississippi found that anti-gay cultural norms served as a barrier to safe sex practices [19]. Another investigation of experiences of homophobic events among Black MSM found that experienced homophobia was a predictor of condomless anal sex within this population [17].…”
Section: Introductionmentioning
confidence: 99%
“…The analyzed productions focused on the provision of specific health services such as the care of the population in cases of HIV, LGBT health care in cases of cancer, health care of transgender people during the transition process, mental health care, health promotion focusing on body weight, smoking cessation program and LGBT aging project (BOHEMER, 2018;MUNRO et al, 2017;CAHILL, 2017;PIERNAAR et al, 2018;GETER et al, 2016;KURTZ;BUTTRAM, 2016).…”
Section: Central Aspects Of Public Health Policies For the Lgbt Popul...mentioning
confidence: 99%
“…In addition to exposing the challenges, the productions focus on aspects of the policy to overcome these problems, such as the promotion of sexual health education for lesbians, gays, bisexuals, transsexuals and transvestites in order to promote empowerment regarding safe sexual practices (GETER et al, 2016).…”
Section: Central Aspects Of Public Health Policies For the Lgbt Popul...mentioning
confidence: 99%
See 1 more Smart Citation